PERSEPSI IMPLEMENTASI MANAJEMEN MEETING INCENTIVE CONVENTION EXHIBITION (Studi Kasus di The SUN Hotel dan ASTON Hotel – Madiun) - Agustinus Doedyk Setiyawan; Eva Mirza Safitri; Aminudin Azis (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2021)
MICE Management consists of event research, event design, event planning, event coordination, and event evaluation, it makes us possible to organize the MICE event. MICE tourism (meeting, incentive, convention, exhibition) or better known as convention tourism has a very large multiplier effect because it can increase economic income and drive other industrial sectors related to the MICE tourism. Industries that will be directly affected by the MICE industry include the hotel industry, the hall supply industry, the restaurant industry and the sound system rental industry. The SUN Hotel and Aston Hotel are among the hotels that provide MICE facilities in the city of Madiun. The hotel has three and four star qualifications with a number of meetingrooms and ballrooms equipped with the necessary equipment and human resources. How and what is the function of the meeting room and ballroom and HR configuration of these two hotels in Madiun City. The conclusions of this study are; The implementation of MICE management at SUN Hotel Madiun based on the results of the analysis of observations, interviews and questionnaires has been done 'well' from all respondents totaling 14 people, over 70% answered agree and strongly agree. Likewise at Aston Hotel Madiun, over 84% answered agreed and strongly agreed.